Strategy Model for the Successful Export Toys of Thai Exporters - Tiranawatananun, Somyos; Sawmong, Sudaporn (Kasetsart Journal of Social Sciences, 2014)
This research was a quantitative research with an objective to search for strategy model for the successful export toys of Thai exporters. Data collection was conducted by using a questionnaire where its validity and reliability were tested. Samples were 380 exporters. Result of searching for strategy model for the successful export toys of Thai exporters by using Structure Equation Model revealed that the structural equation model corresponded to the empirical evidence in a good level with the χ2 = 30.99, df = 22, p-value = 0.096, χ2/df =1.41, RMSEA = 0.032. The strategy model for the successful export toys of Thai exporters consisted of manager’s personality, organization management, marketing mix strategies factors, and operational result of the company. Positive attitude of manager affected the strategic planning of marketing mix and company’s operational result. Good practice of organization management drove the whole organization being operated in the same direction which resulted in increased sales and market share with sustainable growth.